The Hypergeometrical Universe: Cosmogenesis, Cosmology and Standard Model (Global Journal of Science Frontier Research, 2017)
This paper presents a simple and purely geometrical Grand Unification Theory. Quantum Gravity, Electrostatic and Magnetic interactions are shown in a unified framework. Newton's Gravitational Law, Gauss' Electrostatics Law and Biot-Savart's Electromagnetism Law are derived from first principles. Gravitational Lensing and Mercury Perihelion Precession are replicated within the theory. Unification symmetry is defined for all the existing forces. This alternative model does not require Strong and Electroweak forces. A 4D Shock-Wave Hyperspherical topology is proposed for the Universe which together with a Quantum Lagrangian Principle and a Dilator based model for matter result in a quantized stepwise expansion for the whole Universe along a radial direction within a 4D spatial manifold. The Hypergeometrical Standard Model for matter, Universe Topology and a new Law of Gravitation are presented. Newton's and Einstein's Laws of Gravitation and Dynamics, Gauss Law of Electrostatics among others are challenged when HU presents Type 1A Supernova Survey results. HU's SN1a results challenge current Cosmological Standard Model (L-CDM) by challenging its Cosmological Ruler d(z). SDSS BOSS dataset is shown to support a new Cosmogenesis theory and HU proposal that we are embedded in a 5D Spacetime. The Big Bang Theory is shown to be challenged by SDSS BOSS dataset. Hyperspherical Acoustic Oscillations are demonstrated in the SDSS BOSS Galaxy density. A New de-Broglie Force is proposed.
Keywords: cosmology; inflation theory; cosmogenesis; relativity; spacetime